A Large Data Set; Hepatitis B and C Infection in Pregnant Females - Usman Zafar, Aymen Javed, Sumaira Fatima Sabir, Muhammad Asif Naveed, Sufyan Ahmed, Muhammad Zahid Latif (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatitis B and C virus (HBV & HCV) infection is on the surge among pregnant women as a result of unsaved dental and cosmetic procedures, reuse of needles, raising the risk of perinatal transmission and HBV & HCV infection in children. Although few studies on the prevalence of HBV and HCV infection during pregnancy have been conducted but the majority of the studies are on very low sample size. The current study is based on large data set. Objectives: The major goal of this study was to find out the frequency of HBV & HCV in pregnant women. Methods: We conducted a retrospective cohort study in Alkhidmat Raazi Hospital Rawalpindi. A total of 31911 pregnant women who delivered between 2016 and 2021 were analyzed and categorized as HBV & HCV infected or HBV & HCV uninfected by billing codes. The birth certificate and hospital discharge records were used to identify infant records related to HBV and HCV-infected pregnant mothers. Pregnant women’s plasma samples were tested for HBV and HCV using chemiluminescence ARCHITECT i1000SR® Abbott Diagnostics. Data were analyzed using packages within SPSS software and P ≤ 0.05 was considered significant. Cross-tabulation chi-square analysis was performed with a significance level of 5%. Results: The pregnant women with age under 25 years were 12699 (39.8%), women with age from 26 to 29 years were 9734 (30.5%), while women with age 30 and older were 9478 (29.7). The patients who were primigravida were 9514 (29.8%), multipara having 1-4 children 18545 (58.1%) and those having more than five children were 3852 (12.1%). The prevalence of HBV and HCV in 31911 pregnant women were 170/31911 (0.5%) and 478/31911 (1.5%), respectively. The mean age was 27.9 years. Conclusions: HBV and HCV infection is present in pregnant females, which may ultimately increase the treatment cost and vertical transmission. Keywords: Hepatitis B, Hepatitis C, Infection, Pregnant females